Italics and Hispanics in south-west Iberia at the dawn of the Roman-Republican period: The common ware of Monte Molião (Lagos, Portugal) - de Sousa, Elisa; Margarida Arruda, Ana (Rei Cretariae Romanae Fautorum Acta, 2015)
Between 2006 and 2011, archaeological field works that took place in Monte Molião, in the south of Portugal, revealed the existence of an important pre-Roman and Roman settlement. Its human occupation, dated from the last quarter of the 4th century BC to the middle of the 2nd century AD, has provided a very significant set of data.